Understanding the entrepreneur in the growth process: a review and theory. (1st January 2001) - Katz, Jerome A.; Peters, Susan
This paper looks at risk, uncertainty and growth among entrepreneurs, providing a brief review of nearly 40 years of research, and pointing out some of the differences in how researchers and entrepreneurs have looked at these key issues. The goal of this paper is to describe an integrated or holistic way of considering the complex interaction of risk, uncertainty and growth in the entrepreneurial process, and point up some useful areas for further work by researchers, policy-makers, and those who support entrepreneurs in the field.